Interprofessional Education (IPE) in Developing Countries: Challenges and Lesson Learnt from its Implementation in the United Kingdom: A Systematic Review - Sulistyowati, Endah; Walker, Louise (Department of Nursing, Faculty of Medicine, Diponegoro University, 2019)
Background: Evidence of effectiveness of the Interprofessional Education (IPE) in improving collaboration practice, patient and family satisfaction, and patient outcomes had been widely published. Most of developed countries, including United Kingdom, have implemented IPE in their healthcare curriculum, whereas some developing countries are starting the IPE initiative program.Purpose: This study aims to examine the challenges in implementing IPE.Methods: Primary studies to be included in this systematic review were searched fromelectronic databases such as MEDLINE (OVID) 1996, CINAHL, and ERIC (EBSCO). Hand searching through journal of inter-professional care was also conducted. The included studies were critically appraised using JBI QARI appraisal tool. The findings of the included studies were extracted using JBI finding extraction form and appraised based on the JBI level of credibility. The analysis of the study was presented in narrative form.Results: This review produced five qualitative studies using focus groups and interview methods. A total of 5 out of 88 papers met the inclusion criteria included in this systematic review. Three synthesis findings of the challenges in implementing IPE and possible solutions were identified in the literature: inter-professional relationship, IPE curriculum, and administration and resources.Conclusions: The evidence of implementing IPE in developing countries is limited. However, the challenges in implementing IPE in developing countries remain similar with those faced by developed countries. This can be guidance for developing countries to plan, initiate and implement IPE. Future studies about implementation of IPE in developing countries are highly recommended.